Epigenetic programming underpins B‐cell dysfunction in peanut and multi‐food allergy. Issue 8 (24th August 2021) - Imran, Samira; Neeland, Melanie R; Koplin, Jennifer; Dharmage, Shyamali; Tang, Mimi LK; Sawyer, Susan; Dang, Thanh; McWilliam, Vicki; Peters, Rachel; Perrett, Kirsten P; Novakovic, Boris; Saffery, Richard
Abstract: Objective: Rates of IgE‐mediated food allergy (FA) have increased over the last few decades, and mounting evidence implicates disruption of epigenetic profiles in various immune cell types in FA development. Recent data implicate B‐cell dysfunction in FA; however, few studies have examined epigenetic changes within these cells. Methods: We assessed epigenetic and transcriptomic profiles in purified B cells from adolescents with FA, comparing single‐food‐allergic (peanut only), multi‐food‐allergic (peanut and ≥1 other food) and non‐allergic (control) individuals. Adolescents represent a phenotype of persistent and severe FA indicative of a common immune deviation. Results: We identified 144 differentially methylated probes (DMPs) and 116 differentially expressed genes (DEGs) that distinguish B cells of individuals with FA from controls, including differential methylation of the PM20D1 promoter previously associated with allergic disorders. Subgroup comparisons found 729 DMPs specific to either single‐food‐ or multi‐food‐allergic individuals, suggesting epigenetic distinctions between allergy groups. This included two regions with increased methylation near three S100 genes in multi‐food‐allergic individuals. Ontology results of DEGs specific to multi‐food‐allergic individuals revealed enrichment of terms associated with myeloid cell activation. Motif enrichment analysis of promoters associated with DMPs and DEGs showed differential enrichment for motifs recognised by transcription factors regulating B‐ and T‐cell development, B‐cell lineage determination and TGF‐β signalling pathway between the multi‐food‐allergic and single‐food‐allergic groups. Conclusion: Our data highlight epigenetic changes in B cells associated with peanut allergy, distinguishing features of the epigenome between single‐food‐ and multi‐food‐allergic individuals and revealing differential developmental pathways potentially underpinning these distinct phenotypes. Abstract : This study assessed epigenomes and transcriptomes from a cohort of single‐food‐allergic, multi‐food‐allergic and non‐allergic controls. We found distinct B‐cell epigenetic signatures in food‐allergic adolescents and further uncovered multi‐food allergy‐specific methylation signatures, depicting differential regulation of key immune pathways in these clinical groups.